(untitled) (World Bulletin of Management and Law, 2024)
The rise of cryptocurrencies has introduced a paradigm shift in the global financial landscape, challenging traditional notions of currency and finance. This article explores the legal aspects surrounding the use of cryptocurrencies in international transactions, examining the evolving regulatory frameworks and their implications. The decentralized nature of cryptocurrencies, notably exemplified by Bitcoin and Ethereum, presents unique challenges for regulators seeking to strike a balance between fostering innovation and mitigating risks such as money laundering and fraud. This article delves into the diverse approaches taken by countries worldwide to address these challenges, offering insights into the future of legal regulation in the international cryptocurrency sphere and studies the regulation of cryptocurrencies according to legislation of Uzbekistan.